THE GOVERNMENT AND NGOs IN KAZAKHSTAN: STRATEGY, FORMS, AND MECHANISMS OF COOPERATION - DIACHENKO, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2007)
A conspicuous trend in the development of the contemporary world is the growing role of non-governmental organizations (NGOs) in politics, the economy, and sociocultural progress. This phenomenon is typical of most states that are at different levels of socioeconomic and political development. On the whole, the growth of the nongovernmental sector can be characterized as a global phenomenon. An analysis of the entire range of socioeconomic and political changes associated with the growing role of NGOs in the world at the current stage shows that the so-called Third Sector is an important factor of social transformation. Taking into account advanced foreign experience and the current development trends in the world’s leading countries, several widespread sociopolitical changes have occurred in Kazakhstan.ne of the main trends was the change in paradigm of interaction between the government and the nongovernmental sector: the inconsistent dialog of the past has given way to mutually beneficial co-operation. It is a well-known fact that liberalization of the political system in any country is not only aimed at increasing citizens’ participation in sociopolitical life, but also at encouraging their integration in the system of power relations within the framework of the state’s Constitution. One of the main characteristics by which the potential development of a civil society in a particular country can be judged is the ability of its population to carry out sociocultural and political self-organization. In this sense, improvement of the nongovernmental sector is an inalienable attribute of a transforming society, since it directly encourages and expands methods of interaction between civil society institutions and the government. A civil society must be structured in order to function efficiently; therefore, nongovernmental, non-profit associations and organizations are an important part of this society. It stands to reason that the development of a civil society is gauged by the amount, condition, and efficiency of the activity of nongovernmental organizations. It is believed that NGOs can efficiently mediate between the state and its citizens in regulating public relations by fulfilling many important functions in social processes and transformations. The current disputes concern the relations between a civil society and nongovernmental organizations: do NGOs create a civil society, or vice versa? For example, specialists from Freedom House, an Amer-ican nongovernmental organization, believe that a civil society creates conditions for the emergence and activity of NGOs, since they make a civil society more viable.1 Today we are observing the complex and multifaceted formation of the Kazakhstan nongovernmental sector, on which the foundations and traditions of its future enhancement are being built. The logic of Kazakhstan’s further sociopolitical modernization requires building a sustainable civil society in the country at a faster, but qualitative rate. Without the development of this mandatory component of a contemporary civilized state, it will be impossible to achieve further economic and political progress in the country, since the economic, political, and civil spheres form a single system, the elements of which are in intricate, close, and constant interaction with each other.